The Impact of Aging on Macroautophagy in the Pre-ovulatory Mouse Oocyte - Peters, Alexandra E.; Caban, Shandelle J.; McLaughlin, Eileen A.; Roman, Shaun D.; Bromfield, Elizabeth G.; Nixon, Brett; Sutherland, Jessie M. (Frontiers in Cell and Developmental Biology, 2021)
Accompanying the precipitous age-related decline in human female fertility is an increase in the proportion of poor-quality oocytes within the ovary. The macroautophagy pathway, an essential protein degradation mechanism responsible for maintaining cell health, has not yet been thoroughly investigated in this phenomenon. The aim of this study was to characterize the macroautophagy pathway in an established mouse model of oocyte aging using in-depth image analysis-based methods and to determine mechanisms that account for the observed changes. Three autophagy pathway markers were selected for assessment of gene and protein expression in this model: Beclin 1; an initiator of autophagosome formation, Microtubule-associated protein 1 light chain 3B; a constituent of the autophagosome membrane, and Lysosomal-associated membrane protein 1; a constituent of the lysosome membrane. Through quantitative image analysis of immunolabeled oocytes, this study revealed impairment of the macroautophagy pathway in the aged oocyte with an attenuation of both autophagosome and lysosome number. Additionally, an accumulation of amphisomes greater than 10 µm2 in area were observed in aging oocytes, and this accumulation was mimicked in oocytes treated with lysosomal inhibitor chloroquine. Overall, these findings implicate lysosomal dysfunction as a prominent mechanism by which these age-related changes may occur and highlight the importance of macroautophagy in maintaining mouse pre-ovulatory oocyte quality. This provides a basis for further investigation of dysfunctional autophagy in poor oocyte quality and for the development of therapeutic or preventative strategies to aid in the maintenance of pre-ovulatory oocyte health.